Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/nur.22084
|View full text |Cite
|
Sign up to set email alerts
|

Is fall self‐efficacy an independent predictor of recurrent fall events in older adults? Evidence from a 1‐year prospective study

Abstract: Falls, which are prevalent among older adults, may not only cause severe physical injuries, but also lead to low fall self-efficacy (FSE). Low FSE is associated with restricted activity, which putatively increases risk of future falls. However, emerging studies have failed to confirm this association. Furthermore, the interplay between age, gender, and fall history with falls has not been adequately addressed in adults aged 70 years or older. The aims of this secondary analysis were to: (1) prospectively explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Also, impairments in sensorimotor functioning may lead to fear of falls [5] and thus reduction in self-efficacy. Older adults with a higher self-efficacy are at a lower risk of falling and fallers with a lower self-efficacy might be less active in comparison to fallers with greater self-efficacy [16]. This fits with observations by Warner et al [17] and Ryan and Deci [11] who revealed greater autonomy in people with higher self-efficacy.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Also, impairments in sensorimotor functioning may lead to fear of falls [5] and thus reduction in self-efficacy. Older adults with a higher self-efficacy are at a lower risk of falling and fallers with a lower self-efficacy might be less active in comparison to fallers with greater self-efficacy [16]. This fits with observations by Warner et al [17] and Ryan and Deci [11] who revealed greater autonomy in people with higher self-efficacy.…”
Section: Introductionsupporting
confidence: 87%
“…This assumption is in line with Loft et al [15] who indicated that lower fall-related self-efficacy is associated with a higher number of falls in the past [15] and with Warner et al [17] and Ryan and Deci [11] who revealed greater autonomy in people with higher self-efficacy. A recent study by Yang and Pepper [16] confirmed that higher fall-related self-efficacy was significantly correlated with a lower number of falls [16]. Dadgari et al [40] further reported a significant association between low fall-related self-efficacy and high levels of fear of falling and a significant role of self-efficacy as a mediator between falls and fear of falling.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this cohort, ∼12% of subjects reported fall event during the 1-year observation. This rate is relatively low compared to other prospective studies (31,32). The baseline assessment had excluded the older people who had impaired physical mobility and health-related inactivity.…”
Section: Discussionmentioning
confidence: 92%
“…The study design was cross-sectional in 8 studies [16][17][18][19][20][21][22][23] , retrospective in 1 24 , prospective in 10 [25][26][27][28][29][30][31][32][33][34] (with a followup period from 3 months to 3 years) and both retro-and prospective in 1 study 35 . Overall, the majority of the participants of the included studies were females with a percentage ranging from 45% to 84%.…”
Section: Study Design Resultsmentioning
confidence: 99%